Academic Writing Skills (AWS) Perpustakaan Fakultas Psikologi UNDIP dalam Menunjang Keterampilan Literasi Informasi Mahasiswa - Arifah, Mufida Nur; Perdani SP., Nur’aini (Prodi Perpustakaan dan Sains Informasi, 2025)
Information literacy training plays a crucial role in higher education as it helps students familiarize themselves with the academic climate. However, despite being a research-oriented university, the main library of Diponegoro University has not yet implemented organized information literacy training. In contrast, the Faculty of Psychology library at Diponegoro University has taken steps to address this gap through the implementation of the Academic Writing Skills (AWS) program. This study aims to explore how the Library of the Faculty of Psychology, Diponegoro University supports the information literacy skills of its students through the Academic Writing Skills (AWS) program. The research employs a qualitative methodology through interviews and documentation studies. The data collected was analyzed by using thematic analysis. The theory of information literacy standardization for higher education from ACRL was used as a reference in this study. The results showed that the Library of the Faculty of Psychology, Diponegoro University continues to strive for improvement through the development of AWS from what was originally done in a one-shot format to a multi-level format. In addition, material development is carried out which is adjusted to the needs in the field, curriculum, and the level of students' understanding. Librarians continue to discuss and evaluate with elements outside the library such as stakeholders in supporting various developments for their information literacy training. Although there are several evaluations and obstacles in the course process, in general, this training is useful to support student lecture activities.